ENHANCING YOUNG LEARNERS’ PRONUNCIATION THROUGH PHONICS-BASED STRUCTURED ACTIVITIES IN AN EXTRACURRICULAR EFL SETTING - Dewi Rara Amiati; Rahayu Prasetyaningsih; Muhammad Idham Asfar (e-Journal of ELTS (English Language Teaching Society), 2026)
This study examined the effectiveness of phonics-based structured activities in enhancing young learners’ pronunciation in an extracurricular EFL setting. Pronunciation remains a challenging aspect of English learning, particularly for young learners in EFL contexts where exposure to authentic spoken English is often limited. To address this issue, this study implemented a series of phonics-based structured activities designed to improve learners’ pronunciation accuracy, clarity, and word stress. A pre-experimental one-group pretest–posttest design was employed. The participants were 18 elementary students in Grades two and three enrolled in an extracurricular English program at SDN 24 Palu. The intervention was conducted over eight meetings, including one pre-test session, six treatment sessions, and one post-test session, with each session lasting 60 minutes. Data were collected through an oral pronunciation assessment consisting of 12 vocabulary items evaluated across three pronunciation dimensions: accuracy, clarity, and stress. The findings indicated a substantial improvement in students’ pronunciation performance. The mean pre-test score was 62.69, while the post-test mean increased to 85.69. Statistical analysis using a paired-sample t-test revealed that the improvement was significant, t(17) = 8.39, p < .001. These findings suggest that phonics-based structured activities can effectively support pronunciation development among young learners in extracurricular EFL contexts. The study offers practical implications for English educators seeking developmentally appropriate pronunciation instruction for young learners. Keywords: young learners; pronunciation; phonics; extracurricular EFL; pronunciation instruction